A Cross Sectional Study on Bio-Social Status of Women in Reproductive Age Group 18-45 Years in An Urban Community of Kalburgi District, Karnataka: South India - Indupalli, Amrutha Swati; Motakpalli, Kaviraj; Giri, Purushottam A.; Bendigiri, Nazir Ahmed (National Journal of Community Medicine, 2015)
Background Women play significant role in the development of a nation. An attempt is made to ponder over the bio-social status of the women in the society. Method: A community based cross sectional study, among 200 wom- en of reproductive age group (18-45 Years) in the field practice area of KBNIMS, Kalburgi, from 1st April 2014 to 30th June 2014. Result: It’s observed that out of 200 women studied majority were 70% Muslims, 80% belonged to nuclear family, 82% were married 16% were illiterates, 54% and 5% were school dropout and college dropout respectively. The majority (87%) feel that women should contribute to family decisions or decision making, out of which only 77% actually contribute. Conclusion: Age is inversely proportional to health status of women. School dropout and early married women felt the need in the system that could have given them a chance for decision making power on their life. Majority of women are now conscious about education, economic status in society and also freedom of decisions.